Dynamic Young's Modulus and Dimensional Stability of Batai Tropical Wood Impregnated with Polyvinyl Alcohol - Shahidul, Islam; Hamdan, S.; Rahman, M.R.; Jusoh, Ismail; Ibrahim, N.F (JSR Publications, 2010)
Batai tropical wood (paraserianthes molllccana) was impregnated with three levels of poly vinyl alcohol (PVA) solutions (25%,50% and 75%) and the dynanlic Young's modulus, water absorption and dimensional stability of the manufactured wood polymer composites (WPC) were assessed. The modified wood polymer composites (WPC) were characterized by microstructural analysis (Fourier transform infrared spectroscopy and scanning electron microscopy) and free-free vibration testing. The dynanllc Young's modulus (Ed) was calculated using the free-free flexural vibration method. Fourier transform infrared spectroscopy indicated the absorption bands of raw wood to be 1627 cm,l due to carbonyl stretching and WPC show increased absorption band near 1733 cm'l. WPC of 75% PYA solution exhibited improved dimensional stability and lower water absorption. The manufactured WPC yielded a higher Young's modulus compared with the raw one.